Are there too many safe securities? Securitization and the incentives for information production - Hanson, Samuel G.; Sunderam, Adi (Journal of Financial Economics, 2013)
We present a model that helps explain several past collapses of securitization markets. Originators issue too many informationally insensitive securities in good times, blunting investor incentives to become informed. The resulting endogenous scarcity of informed investors exacerbates primary market collapses in bad times. Inefficiency arises because informed investors are a public good from the perspective of originators. All originators benefit from the presence of additional informed investors in bad times, but each originator minimizes his reliance on costly informed capital in good times by issuing safe securities. Our model suggests regulations that limit the issuance of safe securities in good times.